Contribution to the evaluation of safety barriers performance - H HADEF; M DJEBABRA; L SEDRAT; M TAGHLABET (World Journal of Science, Technology and Sustainable Development, 2019)
Purpose The risk control is an unavoidable step in the risk management process. It is materialized by concrete actions of risks reduction in order to decrease their likelihood and/or their severity and also to preserve the environment. The paper aims to discuss this issue. Design/methodology/approach The main goal of the proposed methodology is to define the safety barriers (SB) that can be realized and their contribution to reduce major accidents scenarios that may occur in high-risk establishments. Findings In the proposed methodology, the authors present a combination of methods to prove the effectiveness of SB in an industrial installation. Practical implications The proposed methodology is a valuable help to industrialists to secure their industrial activities and preserve the environment at the same time. Originality/value The retained methods are often used separately for audit purposes or risk assessments of high-risk industrial facilities. In this paper, three methods have been selected and articulated in an approach for a better evaluation of risk control level.